PTU-140 Vedolizumab is an effective therapy in postoperative ileal crohns following loss of response to anti-tnf. (17th June 2017) - Saffouri, E; Kemp, L; Muir, A; Richardson, G; Morrison, P; Watts, D
Abstract : Introduction: Postoperative ileal Crohns disease remains a significant challenge in terms of prevention and treatment once recognised. Many such patients have often lost response to previous anti-TNF exposure prior to surgical intervention and as such their treatment options are limited. Method: The use of Vedolizumab in our cohort of refractory IBD patients was reviewed over the period July 2014 - Nov 2016. Patient demographics and disease phenotype were recorded against duration of treatment with Vedolizumab and clinical outcomes as assessed by a combination of symptom score, endoscopic and radiological response. Previous exposure and outcome to prior anti-TNF therapy was recorded. Results: 37 patients with refractory IBD were identified as eligible for treatment. 2 of these patients were anti-TNF naïve (previous sarcoma/melanoma). Of these, 23 patients had Crohn's disease (10 ileocolonic, 2 ileal, 8 postoperative ileal, 3 colonic disease, 1 gastroduondenal) and 14 patients had ulcerative colitis ( 9 pancolitis, 5 distal colitis). Of the 37 patients, 4 patients had commenced treatment within 12 weeks of review and were discounted from the outcome assessment. Of the patients treated for longer than 14 weeks, clinical response was recorded in 18/20 Crohns patients and 11/13 patients with refractory colitis. Within the postoperative ileal disease group, 6/7 had response to treatment with Vedolizumab following assessment beyond 14 weeks of starting treatment, with 1 patient deemed non-responsive requiring further surgical intervention. Notably, the 1 patient with a combination of postoperative ileal and gastroduodenal disease had mucosal healing at both sites with resolution of gastric outflow obstruction. Conclusion: Vedolizumab is an effective therapeutic strategy in refractory Crohns disease and ulcerative colitis. Response was seen in anti-TNF naïve patients as well as patients with previous primary non-response and secondary loss of response to anti-TNF. In the context of postoperative ileal disease recurrence, this therapy offers a clear effective medical alternative to further surgical resection. The response to Vedolizumab in a single patient with obstructing gastroduodenal Crohns requires further validation in other observational studies. Disclosure of Interest: None Declared